A democracy built on communicative action: Bahá'í political practice as a prefigurative resource for institutional effectiveness, accountability, and inclusivity - Sabet, Michael (Frontiers in Sociology, 2023)
Goal 16 of the UN sustainable development goals, which calls on the global community to “build effective, accountable and inclusive institutions at all levels” (United Nations n.d.), can be conceptualized as aiming at fostering communicative action, a concept developed by Jürgen Habermas to describe a mode for coordinating society grounded in deliberation. However, Habermas simultaneously provides an account of the structural transformation of the public sphere that suggests a hard limit on the capacity of mainstream capitalist liberal democracies to foster genuine communicative action in the relationships between institutions, individuals and communities. This paper therefore argues for the critical role of prefigurative politics, in which communities strive to internally embody desired socio-political forms rather than focusing on changing the wider socio-political order, as a vital resource for generating examples to inform institutional progress. The prefigurative example of the Baha’i community demonstrates norms and practices that may illustrate a path out of the dynamic Habermas identifies of system colonizing lifeworld, by fostering and protecting communicative action as the mode of social coordination. The form of communicative action found in the Baha’i community is situated in a context of a telic-organic model of relationships between individuals, communities and institutions. The paper contrasts the conceptual underpinnings of this model with individualistic conceptions of human nature that are argued to undermine liberal democracy’s capacity for communicative action. At the core of communicative action within a Baha’i context is a distinctive model of deliberation, known within the community as “consultation”. The paper argues that rational-critical consultation can offer a vital nuance to Habermas’ ideal of communicative action as rational-critical debate in the public sphere. The formal democratic structures and processes of the Bahá’í community are also explored as an institutional example that arguably meets the challenge of Goal 16. The paper concludes with initial reflections on a process by which the prefigurative example of a Baha’i model might be brought to bear on institutional performance in wider society.